Loss discrimination algorithm for wired/wireless networks - Seng, Liw Jia; Derahman, Mohd Noor; Abdullah, Azizol (Science Publications, 2011)
Problem statement: Wireless technology has far growing with an increasing demand of the Wireless networking technologies recent years. The wireless access network and cellular networks are being used to support their need. It is usually connected to a wired backbone network. TCP is used to handle the congestion in wired network. However, it is not well suited for hybrid network consisting of wired and wireless networks. Packet loss occurs in wireless network mostly due to high bit error rate, varying in transmission length, or link failure. These scenarios are always misinterpreted by conventional TCP as a congestion loss. Hence, TCP sender performs congestion control which is unnecessary and leads to a poor network performance. Approach: A new algorithm proposed in this study is to differentiate the types of packet loss accurately. The algorithm will classify the packet loss and invoke proper correction mechanisms. Results: Our simulation results show the improvement of TCP performance as compared to the existing Selective-TCP and TCP NewReno. Conclusion: The proposed algorithm on classifying packet loss shows the improvement of TCP performance.